ANALISIS KELAYAKAN BUKU PENILAIAN (BUPENA) DISEKOLAH DASAR - Fitri Puji Rahmawati; Efi Rusdiyani (Profesi Pendidikan Dasar, 2020)
The research objective is to describe the appropriateness of the Assessment Book (Bupena) based on the content, presentation, language, graphics, and moral values contained therein. Bupena is one of the textbooks used by the Surakarta 16 Muhammadiyah Primary School. This research method is a descriptive qualitative method, which produces descriptive data in the form of written words. The research design is book analysis with data analysis techniques in the form of data collection, data recording, data reduction, drawing conclusions, and describing. The validity used is semantic validity. Based on the results of the analysis of the feasibility of the contents or content of the book Bupena presents material that is easy to understand in accordance with the development of students' age, the presentation of books that address the material contextually, the graphics of books that place the illustrations as well-organized explanations, Bupena books included in the category of proper use. The language used in the book is still found errors like mistakes in writing vocabulary. As well as the lack of moral values contained in the book, make a bhasa assessment and the moral values in the Bupena book are inadequate and need improvement.